The Natural History of Facial Schwannomas: A Meta-Analysis of Case Series - Bartindale, Matthew; Heiferman, Jeffrey; Joyce, Cara; Balasubramanian, Neelam; Anderson, Douglas; Leonetti, John (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study is to establish predictors of facial paralysis and auditory morbidity secondary to facial schwannomas by assimilating individualized patient data from the literature.Design A systematic review of the literature was conducted for studies regarding facial schwannomas. Studies were only included if they presented patient level data, House–Brackmann grades, and tumor location by facial nerve segment. Odds ratios (OR) were estimated using generalized linear mixed models.Main Outcome Measures Facial weakness and hearing loss.Results Data from 504 patients were collected from 32 studies. The geniculate ganglion was the most common facial nerve segment involved (39.3%). A greater number of facial nerve segments involved was positively associated with both facial weakness and hearing loss, whereas tumor diameter did not correlate with either morbidity. Intratemporal involvement was associated with higher odds of facial weakness (OR = 4.78, p < 0.001), intradural involvement was negatively associated with facial weakness (OR = 0.56, p = 0.004), and extratemporal involvement was not a predictor of facial weakness (OR = 0.68, p = 0.27). The odds of hearing loss increased with more proximal location of the tumor (intradural: OR = 3.26, p < 0.001; intratemporal: OR = 0.60, p = 0.14; extratemporal: OR = 0.27, p = 0.01).Conclusion The most important factors associated with facial weakness and hearing loss are tumor location and the number of facial nerve segments involved. An understanding of the factors that contribute most heavily to the natural morbidity can help guide the appropriate timing and type of intervention in future cases of facial schwannoma.
Keywords: facial schwannoma; facial nerve; facial palsy; hearing loss; parotid neoplasm; temporal bone neoplasm; cerebellopontine angle neoplasm